ARTIFICIAL INTELLIGENCE IN ORTHODONTICS: A REVIEW - Dr. MONJEET GOSWAMI, Dr. Ashutosh, Dr. Yasir Ayub, Dr. Rahul Sinha, Dr. Ekta Suman, Dr. Sanjana Baisoya (South Eastern European Journal of Public Health, 2025)
Artificial Intelligence (AI) is revolutionizing various medical fields, including orthodontics. Its applications range from diagnosis and treatment planning to predicting treatment outcomes and enhancing patient management. This review highlights the advancements in AI technologies within orthodontics, exploring machine learning, deep learning, and their implications on clinical practice.